Pengembangan Buku Ajar Matematika Terintegrasi Nilai-Nilai Keislaman dalam Penanaman Karakter Siswa Madrasah Ibtidaiyah - Kholil, Mohammad; Usriyah, Lailatul (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
Teaching materials is one important component in learning. Teaching material is packaged in an interesting learning resource so that it can help cultivation of character in student, especially elementary school students. At this age is the right time to instill the concept in children, especially concepts related to character. This is a challenge for teachers to be able to integrate concepts in subject matter with Islamic values that can help grow student character. Therefore, in this study the development of mathematics textbooks that integrated Islamic values in the character planting of Madrasah Ibtidaiyah Zainul Hasan Balung students was carried out. The purpose of this study is 1) to explain the process of compiling mathematics textbook that integrated Islamic values for the cultivation of characters in students of Madrasah Ibtidaiyah Zainul Hasan Balung; and 2) Knowing the feasibility of mathematics textbooks that integrated Islamic values for the cultivation of character in students of Madrasah Ibtidaiyah Zainul Hasan Balung. The approach and type of research used in this study is Research and Development (RD). Research and development are a research method used to produce certain products and test the effectiveness of these products. This research was designed using the Borg W.R. and Gall M.D. textbook development model. The development of this teaching material produces mathematics textbooks integrated Islamic values as a teacher and student companion book in learning mathematics. The resulting textbooks were tested on third grade studentâ€™s â€œAâ€ of MI Zainul Hasan Balung. Trial of mathematics textbook products that integrated Islamic values to find out the attractiveness or feasibility of textbooks. From the calculations using formulas, the percentage of feasibility or attractiveness of the use of mathematics textbooks that integrated Islamic values is 84.30%. In accordance with the table of eligibility or validity shows that the results of the validation or the feasibility of developing a mathematic textbook that integrated Islamic values included in the category is very interestingÂ